The Size Effect Anomaly in the Indian Stock Market - Patel, Jayen B. (Journal of Applied Business and Economics, 2024)
The size effect in stock market implies that small firm stocks generate higher risk-adjusted returns from that of large firm stocks. We did not find a size effect in the Indian stock market for the period of October 2005 to September 2023. We also examined the prevalence of size effect separately by calendar months. Small firm stocks generated significantly higher returns from than of large firms in April and December. Alternately, we did not find a size effect during January, November-December and March to May. We conclude only April and December months’ exhibit a size effect in the Indian stock market.